2014
DOI: 10.5051/jpis.2014.44.4.158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of scaling and root planing on C-reactive protein levels in gingival crevicular fluid and serum in chronic periodontitis patients with or without diabetes mellitus

Abstract: PurposeThe present study was conducted to evaluate the impact of scaling and root planing (SRP) on the C-reactive protein (CRP) levels of gingival crevicular fluid (GCF) and serum in chronic periodontitis patients with type 2 diabetes mellitus (T2DM-CP) or without type 2 diabetes mellitus (NDM-CP).MethodsForty-eight human participants were divided into two groups: an experimental (T2DM-CP) group (group I, n=24) comprising chronic periodontitis patients with random blood sugar ≥200 mg/dL and type 2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
7
26
0
Order By: Relevance
“…The levels of hs-CRP and IL-6 are increased in both MetS and chronic periodontitis (6,31) and are decreased after periodontal treatment (32,33). Similarly to the results of the present study, it was reported that CRP levels decreased after NSPT (34)(35)(36)(37). In this study, the baseline serum levels of hs-CRP and IL-6 were significantly higher in the MetS group than in the SH group and decreased * p<0.05, significant difference compared to baseline, p<0.05, significant difference compared to 3 M § p<0.05 significant difference between groups 3 M = 3 rd Month 6 M = 6 th Month Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The levels of hs-CRP and IL-6 are increased in both MetS and chronic periodontitis (6,31) and are decreased after periodontal treatment (32,33). Similarly to the results of the present study, it was reported that CRP levels decreased after NSPT (34)(35)(36)(37). In this study, the baseline serum levels of hs-CRP and IL-6 were significantly higher in the MetS group than in the SH group and decreased * p<0.05, significant difference compared to baseline, p<0.05, significant difference compared to 3 M § p<0.05 significant difference between groups 3 M = 3 rd Month 6 M = 6 th Month Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The levels of hs‐CRP and IL‐6 are increased in both MetS and chronic periodontitis and are decreased after periodontal treatment . Similarly to the results of the present study, it was reported that CRP levels decreased after NSPT . In this study, the baseline serum levels of hs‐CRP and IL‐6 were significantly higher in the MetS group than in the SH group and decreased significantly in both groups after NSPT.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it has been reported that serum CRP level may decrease after successful periodontal treatment or DM treatment . Mohan et al reported that there was a greater reduction in serum CRP levels after periodontal treatment in T2DM patients than in non‐DM patients. Lalla et al reported that there was a significant decrease in serum CRP levels after periodontal treatment in patients with DM and CP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2MD are affected by CP, and their increased levels of inflammatory factors enhance insulin resistance [22]. It has been suggested that with treatment, C-creative protein (CRP) in CP patients with T2DM greatly decreases and that the control of the inflammatory responses associated with CP is helpful to the control of blood glucose in these patients [23]. In this study, the pattern of changes in FPG and HbA1c in the study group and the control group shows that semiconductor laser-assisted minocycline therapy in treating CP was able to control blood glucose, weaken the effect of hyperglycemia on the periodontal tissues, and enhance the therapeutic effect of CP.…”
Section: Discussionmentioning
confidence: 99%